Die Beziehungen der Norddeutschen Wollkämmerei und Kammgarnspinnerei zu den Banken - Harald Wixforth (IBF - Institut für Bank- und Finanzgeschichte, 2017)
The Relationship of the Norddeutsche Wollkämmerei und Kammgarnspinnerei (Nordwolle Group) with the Banks: Research into the relationship between banking and industry has long held the view that banks had dominated their clientele from industry, trade and retailing and they had established a position of power that was almost impossible to reign in. More recent studies question this assessment and deliver impressive evidence that the relationship between industry and banks was often characterized by information asymmetries. For example, major companies often withheld information about their earnings performance during credit negotiations so that the banks had to make large risk provisions which reduced their profitability. This was also true for the Nordwolle textile group, which had financed the expansion of its business during the Weimar Republic primarily from outside capital, first and foremost using loans from various banks. In obtaining these loans, the Group's management succeeded repeatedly in playing competing banks against one another. Even major banks such as Danat-Bank, Berliner Handelsgesellschaft, and probably Dresdner Bank as well, placed major bets on getting Nordwolle to commit itself as a client. As long as the banks could be talked into believing that company was profitable and continually expanding, the banks were ready to grant new loans. Not until the spring of 1931, after indications about the Group's actual situation had made the rounds did the banks push through extensive audits of the company's financial statements. That the efforts to rescue Nordwolle ultimately remained fruitless was not least a result of the new-found caution in awarding additional loans.
Keywords: G21; G31; G32; G33; L14; L67; N24; N44; 330